Ответ:
Объяснение:
3[tex]\sqrt{3}[/tex]-8[tex]\sqrt{3}[/tex]+15[tex]\sqrt{3}[/tex]=
[tex]\sqrt{3^{2}*3 }[/tex]-[tex]\sqrt{8^{2}*3 }[/tex]+[tex]\sqrt{15^{2}*3}[/tex]=
[tex]\sqrt{27}[/tex]-[tex]\sqrt{192}[/tex]+[tex]\sqrt{675}[/tex]=
[tex]\sqrt{27-192+675}[/tex]=
[tex]\sqrt{510}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
3[tex]\sqrt{3}[/tex]-8[tex]\sqrt{3}[/tex]+15[tex]\sqrt{3}[/tex]=
[tex]\sqrt{3^{2}*3 }[/tex]-[tex]\sqrt{8^{2}*3 }[/tex]+[tex]\sqrt{15^{2}*3}[/tex]=
[tex]\sqrt{27}[/tex]-[tex]\sqrt{192}[/tex]+[tex]\sqrt{675}[/tex]=
[tex]\sqrt{27-192+675}[/tex]=
[tex]\sqrt{510}[/tex]